Effect of extremely low frequency magnetic field on enamel microhardness in rats - (:unkn) unknown (ARIESDUE SRL, 2011)
Aim The potential effects on human health of extremely low frequency magnetic field (ELF-MF) are of considerable concern. In the present study it was investigated the effect of long term ELF-MF exposure on microhardness of rat teeth. Materials and methods Thirty male Sprague-Dawley rats were divided into three groups. The first and second experimental groups (n=10) were exposed to 100 mu T and 500 mu T ELF-MF during 10 months, 2 hours a day respectively For the control group, nothing was applied to the rats and they completed their life cycle in the cage during the study period. After ELF-MF exposure, microhardness of enamel surface was determined for each group. Results The decrease in microhardness in the second experimental group was found to be statistically significant compared to the control group (P<0.05). However, no statistical difference was found between the first and second experimental groups (P>0.05). Conclusion From the results it can be concluded that 500 mu T level of magnetic field strengths may have a certain negative effect on enamel mineralisation. Further investigations are necessary to analyse the effect of ELF-MF on teeth.
Keywords: Magnetic field; Enamel; Microhardness; TRACE-ELEMENTS CONTENT; BONE-DENSITY CHANGES; ELECTROMAGNETIC-FIELDS; OSTEOPOROSIS; TEETH; REMINERALIZATION; EXPOSURE; CELLS; MODEL